Electrochemical detection of ursolic acid from spruce (Picea abies) essential oils using modified amperometric microsensors. (22nd September 2019) - Oancea, Ioana Adina; van Staden, Jacobus (Koos) Frederick; Oancea, Elena; Ungureanu, Eleonora-Mihaela
Abstract: Ursolic acid (UA) is a natural pentacyclic triterpenoid carboxylic acid found in some medicinal plant species. In this paper, amperometric microsensors based on a powder which contained graphite (G) and carbon nanoparticles (CN) (G-CN) unmodified and modified with chitosan (CHIT) and tetraphenyl-porphine cobalt(II) (Co(II)TPP) are proposed for the analysis of UA plant source essential oils obtained from spruce ( Picea Abies ). Differential pulse voltammetry (DPV) was used to optimize the method and for the determination of ursolic acid from different types of botanical samples. The optimum working pH was 5.00 for the G-CN and (Co(II)TPP)/G-CN microsensors and pH 3.00 for CHIT/G-CN in the presence of a 0.1 mol L −1 KCl supporting electrolyte. The linear concentration ranges for ursolic acid (UA) were between 0.1 and 100 µmol L −1 for the unmodified microsensor (G-CN), 0.01, 1 µmol L −1 for the microsensor modified with chitosan (CHIT/G-CN), and 0.01 and 10 µmol L −1 for the microsensor modified with (Co(II)TPP)/G-CN). It is the first time these amperometric microsensors have been used for the reliable analysis of ursolic acid (UA) in three original botanical samples obtained from different parts of spruce ( Picea abies ): resin essential oil, cons essential oil, cons and sprouts essential oil, with recovery rate values up to 99.29%.